A surface-enhanced electrochemiluminescence sensor based on Au-SiO2 core–shell nanocomposites doped with Ru(bpy)32+ for the ultrasensitive detection of prostate-specific antigen in human serum. Issue 1 (20th November 2019) - Wang, Daifang; Zhou, Jin; Guo, Longhua; Qiu, Bin; Lin, Zhenyu
Abstract : This study reports a surface-enhanced electrochemiluminescence (SEECL) sensor for the ultrasensitive detection of prostate-specific antigen (PSA) in human serum. Abstract : This study reports a surface-enhanced electrochemiluminescence (SEECL) sensor for the ultrasensitive detection of prostate-specific antigen (PSA) in human serum. First, we prepared the Au-SiO2 core–shell nanocomposites doped with Ru(bpy)3 2+ (Au@SiO2 -Ru) as the ECL signal generation and amplification element of the SEECL sensor. Ru(bpy)3 2+ could emit ECL under the excitation of an electrochemical reaction, and generate the local surface plasmon resonance (LSPR) electromagnetic field from the gold nanoparticle (AuNP) core. The produced LSPR then effectively enhanced the ECL signals. This sensing strategy was utilized for the detection of PSA, which can be absorbed on the electrode surface by the reaction between PSA and monoclonal antibodies. When polyclonal antibody-modified Au@SiO2 -Ru was added, the PSA-double-antibody sandwich structure was formed on the electrode surface and thus, the Au@SiO2 -Ru were quantitatively immobilized on the electrode surface. The results show that this kind of SEECL sensor has good selectivity toward PSA. Notably, the minimum detection concentration reached 7 × 10 −7 ng mL −1 under the optimum experimental conditions, which is much better than most of the previously reported approaches for the detection of PSA in serum.